Comment of article “The pain ratio before and afterthe application of physiotherapy for dysfunction oftemporomandibular joint” (Journal of Health Sciences, 2025)
Dear Editor,I have read the article entitled ''The pain ratio before and after physiotherapy for dysfunction of temporo mandibular joint"' by Hadzic et al. I would like to comment on this article in terms of its strengths, weaknesses and future perspectives. I believe that this additional letter will make this article more comprehensive and interesting.